Effect of oil prices to the emerging stock market in Latin America and Caribbean (Argentina, Brazil and Jamaica) / Nur Afiqah Ali Rahman - Ali Rahman, Nur Afiqah (2010)
This study tries to investigate the relationship between oil prices and stock market in emerging markets of Latin America region. Data of weekly West Texas Intermediate Crude Oil (WTI) price and weekly price index of stock index from three emerging countries namely Argentina, Brazil and Jamaica are selected as variables in this study. The data is collected for the five years period of 1 January 2005 to 31 December 2009and used to estimate the Auto regression Model. The results from this model reveal that there is significant and relationship between these two emerging markets where is Argentina and Jamaica with the oil price movement. Furthermore, the analysis also shows Brazil has a relationship with oil price but there is no significant result due to the more significant on other macroeconomic variable. These results further our understanding of the interaction between oil prices and share prices and should be of use to investors, regulator, managers, and policy maker.